2017
DOI: 10.1038/bjc.2017.169
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-associated breast cancer and gonadal hormone exposure: a report from the Childhood Cancer Survivor Study

Abstract: Background:The relationship between hormone exposure and breast cancer risk in women treated with chest radiotherapy for childhood cancer is uncertain.Methods:Participants included 1108 females from the Childhood Cancer Survivor Study who were diagnosed with childhood cancer 1970–1986, treated with chest radiotherapy, and survived to ages ⩾20 years. Hazard ratios (HRs) and 95% confidence intervals (CIs) from Cox models adjusted for chest radiation field, delivered dose, anthracycline exposure, and age at child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 35 publications
0
21
2
Order By: Relevance
“…In the current study, the radiation risks did not vary significantly by menopause-related variables including age at menopause and number of reproductive years, a surrogate measure of ovarian function and breast tissue exposure to estrogens. By contrast, several published studies of childhood cancer survivors exposed to high radiation doses to the chest showed higher breast cancer risks with late menopause (40 years) compared to early menopause (,40 years) and 10 years of ovarian function after radiotherapy compared to ,10 years (14,43). Comparison of radiation risks with childhood cancer survivors is complicated by the fact that some patients might experience premature ovarian failure due to pelvic irradiation (40) or alkylating agents (HD patients) and are exposed around menarche (7,43,44); in addition, attained age of childhood cancer survivors (14, 23) is substantially lower than the current LSS cohort.…”
Section: Effects Of Reproductive and Other Factors On Radiation Risksmentioning
confidence: 83%
“…In the current study, the radiation risks did not vary significantly by menopause-related variables including age at menopause and number of reproductive years, a surrogate measure of ovarian function and breast tissue exposure to estrogens. By contrast, several published studies of childhood cancer survivors exposed to high radiation doses to the chest showed higher breast cancer risks with late menopause (40 years) compared to early menopause (,40 years) and 10 years of ovarian function after radiotherapy compared to ,10 years (14,43). Comparison of radiation risks with childhood cancer survivors is complicated by the fact that some patients might experience premature ovarian failure due to pelvic irradiation (40) or alkylating agents (HD patients) and are exposed around menarche (7,43,44); in addition, attained age of childhood cancer survivors (14, 23) is substantially lower than the current LSS cohort.…”
Section: Effects Of Reproductive and Other Factors On Radiation Risksmentioning
confidence: 83%
“…Although the literature in CCS on this subject is very limited, the result of the Childhood Cancer Survivor Study was very reassuring, i.e. they reported that survivors with POI and treatment with estrogen replacement therapy have lower risk to develop breast cancer than the CCS without POI [54]. …”
Section: Treatment Of Gonadal Insufficiency (Primary and Central)mentioning
confidence: 99%
“…Conversely, the adverse impact of cancer treatments on female reproductive function increases with older age at exposure because of the natural decline in oocyte number with age, leading to sterility at lower doses or premature ovarian failure at shorter intervals posttherapy . In addition, recent evidence suggests that the association between chest radiation and increased breast cancer risk is highest when exposure occurs near the time of menarche . Although these patient‐specific factors are not modifiable, understanding their impact informs the selection of frontline treatments for diseases in which more than one equally efficacious approach is available as well as surveillance and prevention strategies among survivors.…”
Section: Patient‐specific Demographic Factorsmentioning
confidence: 99%
“…For example, only 31% of childhood cancer survivors with premature ovarian insufficiency (POI) reported receiving hormone‐replacement therapy in the SJLIFE cohort, whereas POI was independently associated with poor bone mineral density and frailty in the same study . Furthermore, data remain limited regarding the safety and long‐term benefit of certain interventions, such as growth hormone replacement in adults or sex hormone replacement in women experiencing premature menopause . Although the initiation of hormone‐replacement therapy (HRT) for females in the general population with POI is recommended, with guidance to continue until the age of natural menopause, there is not a clear consensus for HRT in childhood cancer survivors.…”
Section: Interaction Of Cancer Therapy With Premorbid and Comorbid Comentioning
confidence: 99%
See 1 more Smart Citation